2013
DOI: 10.1039/c3tc31288g
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermally synthesized oxalate and phenanthroline based ferrimagnetic one-dimensional spin chain molecular magnets [{Fe(Δ)Fe(Λ)}1−x{Cr(Δ)Cr(Λ)}x(ox)2(phen)2]n (x = 0, 0.1 and 0.5) with giant coercivity of 3.2 Tesla

Abstract: Hydrothermally synthesized oxalate and phenanthroline based ferrimagnetic one-dimensional spin chain molecular magnets [{Fe(D)Fe(L)} 1Àx {Cr(D) Cr(L)} x (ox) 2 (phen) 2 ] n (x ¼ 0, 0.1 and 0.5) with giant coercivity of 3.2 Tesla

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 73 publications
3
13
0
Order By: Relevance
“…Well-defined Bragg peaks are observed in the neutron diffraction patterns. No significant change is observed in the intensities of the Bragg peaks down to 15 K. The magnetization data also suggest that the compound is paramagnetic at 15 K. However, the diffraction pattern at 2 K, when the compound is in the magnetic state, shows an extra peak (001) around ∼13° along with enhancement in the other Bragg peak intensities. Therefore, the neutron diffraction patterns of the compound up to 15 K belong to the paramagnetic state, and an enhancement of Bragg peaks will appear in the neutron diffraction patterns after the magnetic ordering sets below the transition temperature of the compounds which is 8.7 K for the x = 0 compound.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…Well-defined Bragg peaks are observed in the neutron diffraction patterns. No significant change is observed in the intensities of the Bragg peaks down to 15 K. The magnetization data also suggest that the compound is paramagnetic at 15 K. However, the diffraction pattern at 2 K, when the compound is in the magnetic state, shows an extra peak (001) around ∼13° along with enhancement in the other Bragg peak intensities. Therefore, the neutron diffraction patterns of the compound up to 15 K belong to the paramagnetic state, and an enhancement of Bragg peaks will appear in the neutron diffraction patterns after the magnetic ordering sets below the transition temperature of the compounds which is 8.7 K for the x = 0 compound.…”
Section: Resultsmentioning
confidence: 78%
“…The room-temperature X-ray and neutron diffraction studies revealed the 1D nature of chains comprising alternating Fe 1 (Δ)- and Fe 2 (Λ)-assembled building units. The dc magnetization measurements showed spontaneous magnetization below ∼9 K. The transition temperatures were found to be ∼8.7, 8.2, and 4.0 K for x = 0, 0.1, and 0.5 compounds, respectively . However, the magnetization versus magnetic field curves for all these compounds did not show any saturation even under an applied magnetic field of 9 T and could be associated with a canted AFM behavior.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…For example, the compounds synthesized using nitronyl nitroxides, imino nitroxides, and butyl nitroxide ligands with metal ions {metal­(II) bis-hexafluoroacetylacetonate} form chains (1-D), layers (2-D), and bulk networks (3-D). In this regard, we have synthesized molecule-based magnets of Prussian blue analogues, chain molecular magnets, and single-molecule magnets using coprecipitation and hydrothermal methods. …”
Section: Introductionmentioning
confidence: 99%